Translation, Exegesis, and 1 Thessalonians 2.14–15: Could a Comma Have Changed the Course of History? - Porter, Stanley E. (The Bible translator, 2013)
This article examines recent commentaries and translations of 1 Thessalonians 2:14-15, especially the issue of whether the clause describing the Jews is restrictive or not. The author argues that some recent scholarship shows that the clause should be taken as restrictive, but that a number of recent commentaries and translations—although with some encouraging exceptions—have failed to take this into account. This interpretation, which entails punctuation without a comma at the end of v. 14 (in English and Greek), clarifies a number of exegetical problems.